The Effectiveness of E-Recruitment Process using Job Vacancies Applications in the Digitalization Era - Krisna Wira Setiawan, I Made; Bagus Teddy Prianthara, Ida (Quantitative Economics and Management Studies, 2024)
The rapid development of information technology has brought significant changes in various aspects of life, including the recruitment process. This research aims to analyze the role of technology in increasing the effectiveness and efficiency of the e-recruitment process through the use of job vacancy applications in the digitalization era. The method used in this research is a literature study and survey of companies that have implemented e-recruitment technology. The research results indicate that the use of technology in e-recruitment not only speeds up the candidate search and selection process, but also improves the quality of recruited candidates through a better screening system. In addition, job vacancy applications facilitate access to information and communication between companies and prospective applicants, thereby creating a more transparent and satisfying recruitment experience. This research concludes that technology plays a crucial role in modernizing and optimizing the recruitment process, which in turn contributes to achieving organizational goals more effectively and efficiently.